(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2023)
The article is about the works of Kazimierz Braun - stage director, expert in the field of theatre, author of literary works. It recalls this artist and researcher as a theatre authority, but also it shows the authorities that formed him as an artist. Moreover, this text reveals the meaning of the figure of authority in Braun’s literature on the example of the biographical dramas he wrote. The main purpose of this article is to analyse the influence of authorities on Braun’s understanding of artistic activity, his creative strategy and its implementation in selected cultural texts. The terms of authority as a task, a challenge and an obligation in the title of the article referred to different areas of Braun’s activity, which, on the one hand, indicate the impact of authority, but on the other hand, show the way to gain it.